New criteria in defining the metabolic syndrome in children – an analysis of the relationship between the hepatic enzymes and the insulin resistance, HOMA-IR, glucose tolerance test in the obese children - Pelin, Ana-Maria; Balan, Gabriela; Stefanescu, Cristina; Rosca, Stefan; Busila, Camelia (Progress in Nutrition, 2022)
Method: 108 children aged between 7 and 18 years old (12.89±2.93), with body mass index - BMI > 25 kg/m2 were studied, who underwent metabolic syndrome parameters’ assessments. Determinations of blood pressure, abdominal perimeter, fasting glucose, OGTT (oral glucose tolerance test -2-h G), insulinemia were made, the HOMA-IR index (Homeostatic model assessment for insulin resistance) was calculated. The value of the HOMA-IR index between 2-4 was considered as glucose tolerance decrease and HOMA-IR>4 was considered diabetes for both sexes. We also made laboratory determinations of cholesterol, HDL-cholesterol, LDL-cholesterol, triglycerides. We correlated the identified groups with diabetes mellitus and the glucose tolerance decrease according to HOMA-IR and OGTT with the values of liver enzymes AST (aspartataminotransferase) and ALT (alaninaminotransferase).Results: The calculated HOMA-IR showed, in 53.7% of the obese children, the glucose tolerance decrease, (HOMA-IR > 2). The individual level of the HOMA-IR index was significantly lower at older ages, the correlation was indirect, moderate in intensity (r = - 0.217; p=0.024), suggesting that approximately 22% of children have a lower HOMA-IR level at older ages. The following are confirmed as good predictors of diabetes: LDL cholesterol (AUC=0.632; IC95%: 0.526-0.738; p=0.018), ALT (AUC=0.645; IC95%: 0.541-0.750; p=0.009) and AST (AUC=0.617; IC95%: 0.510-0.724; p=0.036). The HDL cholesterol parameter proves to be a good predictor of decreased glucose tolerance (AUC=0.607; IC95%: 0.469-0.745)Conclusions: The increased liver enzymes (mainly AST, but also ALT) and LDL cholesterol are positively associated with the prevalence of the metabolic syndrome (MS) in paediatric populations and with diabetes mellitus. Although there is a correlation between AST, ALT and LDL-cholesterol and decreased glucose tolerance or diabetes mellitus, a larger batch analysis of obese children is required to determine whether liver enzymes and LDL-cholesterol can be introduced as diagnostic criteria of the MS.KEYWORDS: obesity, child, glucose tolerance decrease, hepatic enzymes